3D ordered macroporous NiO/Al nanothermite film with significantly improved higher heat output, lower ignition temperature and less gas production. (15th November 2016) - Yu, Chunpei; Zhang, Wenchao; Shen, Ruiqi; Xu, Xing; Cheng, Jia; Ye, Jiahai; Qin, Zhichun; Chao, Yimin
Abstract: The performances of nanothermites largely rely on a meticulous design of nanoarchitectures and the close assembly of components. Three-dimensionally ordered macroporous (3DOM) NiO/Al nanothermite film has been successfully fabricated by integrating colloidal crystal template (CCT) method and controllable magnetron sputtering. The as-prepared NiO/Al film shows uniform structure and homogeneous dispersity, with greatly improved interfacial contact between fuel and oxidizer at the nanoscale. The total heat output of 3DOM NiO/Al nanothermite has reached 2462.27 J·g − 1 at optimal the deposition time of 20 min, which is significantly more than the values of other NiO/Al structural systems that have been reported before. Intrinsic reduced ignition temperature (onset temperature) and less gas production render the wide applications of 3DOM NiO/Al nanothermite. Moreover, this design strategy can also be readily generalized to realize diverse 3DOM structured nanothermites. Graphical abstract: Highlights: 3D ordered macroporous NiO/Al nanothermite synthesised by integrating colloidal crystal template and magnetron sputtering. The morphology and heat release of the designed nanomaterials can be controlled by different aluminizing times. Significantly enhanced energy output, with 71.5% of the theoretical value, increased by 260-1530 J·g − 1 than other systems. Obtained NiO/Al system exhibits lowered ignition temperature (about 460 °C), reduced impurities and less gas production. This NiO/Al nanothermite film has the great potential applications in the field of microinitiators.